2020
DOI: 10.2478/hukin-2019-0096
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Recommendations for Physique Athletes

Abstract: The popularity of physique sports is increasing, yet there are currently few comprehensive nutritional guidelines for these athletes. Physique sport now encompasses more than just a short phase before competition and offseason guidelines have recently been published. Therefore, the goal of this review is to provide an extensive guide for male and female physique athletes in the contest preparation and recovery period. As optimal protein intake is largely related to one’s skeletal muscle mass, current evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 201 publications
(299 reference statements)
1
81
0
1
Order By: Relevance
“…If a low carbohydrate intake has affected muscle gain, it did not alter muscle performance. Strength and power athletes are recommended to maintain a higher carbohydrate intake (3–8 g/kg) [ 53 , 54 , 55 ] to sustain the intramuscular glycogen stores and engage in greater training volume. It has been observed that during KD regimen muscle glycogen stores can decrease by ~40–50% [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…If a low carbohydrate intake has affected muscle gain, it did not alter muscle performance. Strength and power athletes are recommended to maintain a higher carbohydrate intake (3–8 g/kg) [ 53 , 54 , 55 ] to sustain the intramuscular glycogen stores and engage in greater training volume. It has been observed that during KD regimen muscle glycogen stores can decrease by ~40–50% [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that these nutritional recommendations were obtained for bodybuilders, whose body fat percentage tends to be lower during the season. Moreover, the magnitude of the energy deficit [19], the rate of BM loss per week [20], nutritional considerations such as timing, protein intake, etc., and the body composition assessment methods employed could help explain FFM variations along the weight loss phase.…”
Section: Discussionmentioning
confidence: 99%
“…Tables are presented changes from Baseline 1 to 16-weeks (pre-competition) were calculated in tables for unit change (△) and percent change (△%). Recommended or normal ranges were provided when appropriate for comparison from the ABIM Laboratory Test Reference Ranges and other qualifying references and organizations [ 13 , 14 , 17 , 38 , 39 , 45 – 47 ]. Additionally, both the 4-day dietary recall and RMR data were expressed in both kcal·d − 1 and kcal·kgLBM − 1 ·d − 1 to control for participant LBM differences to compare to any notable recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…They found that competitors that did not use hormone contraceptives had greater menstrual irregularity than those that reported use. Dietary analysis showed that both groups’ CHO intake was below ACSM recommendations for moderate training athletes (5–7 g·kg − 1 ·d − 1 ) [ 13 ], yet within the ‘ realistic ’ range (2–5 g·kg − 1 ·d − 1 ) proposed by Roberts, et al for physique athletes, which is dependent on the phase of training [ 14 ]. However, there is currently no established and widely accepted daily CHO intake recommendation for physique competitors.…”
Section: Introductionmentioning
confidence: 99%